Efficacy of ATG and Rituximab in capuchin monkeys (a New World monkey)–An in vitro study relevant to xenotransplantation. (28th June 2020) - Yamamoto, Takayuki; Ladowski, Joseph M.; Bikhet, Mohamed; Cooper, David K. C.; Hara, Hidetaka
Abstract: While Old World monkeys, for example, baboons, have antibodies against triple‐knockout (TKO) pig cells, thus complicating pig organ transplantation studies, capuchin monkeys (a New World monkey) do not, thus more closely mimicking humans in respect to the response to TKO pig cells. Whether drugs such as anti‐thymocyte globulin (ATG) and Rituximab are effective in capuchin monkeys remains uncertain. We measured the binding and cytotoxicity of ATG and Rituximab to human (n = 7), baboon (n = 7), and capuchin monkey (n = 5) peripheral blood mononuclear cells (PBMCs), T cells or B cells by flow cytometry.The effect in vitro of ATG in depleting PBMCs in capuchin monkeys and baboons was significantly less than in humans, but the depletion in capuchin monkeys was not significantly different from that in baboons. In contrast, the effect in vitro of Rituximab in depleting B cells in capuchin monkeys was very limited, and significantly less than in humans and baboons.Although capuchin monkeys mimic the human antibody response to TKO pig cells more closely than baboons, Rituximab had a minimal effect in capuchin monkeys in vitro. This observation may limit the value of New World Monkeys as recipients of pig organs, tissues, or cells in experimental studies of xenotransplantation or, indeed, in allotransplantation.